IMPLEMENTASI PERATURAN DAERAH TENTANG PELAYANAN PUBLIK DI KOTA SURABAYA - Windiani (Jurnal Sosial Humaniora, 2025)
This research aim to know about interpretation and implementation low of Public Service in Surabaya. This is qualitatif research and take many public officials as informan with snowball sampling methode. This research show that implementation law of public service not opptimaly because many resion: there are not minimum standart public services, quality of human resoursches, and carrying capacity of services not good. Beside that, there is not guide line to interpretation about low of public servise, so many officials have problems to implentation. So, needed change paradigm of public officials that they should give service not serviced by public. But, in generally, many officials public services aware that low of public servises in Surabaya is commitment type by government to increase quality of public service espesialy for Surabaya citizen.